2015
DOI: 10.3389/fpls.2015.00775
|View full text |Cite|
|
Sign up to set email alerts
|

How and why do root apices sense light under the soil surface?

Abstract: Light can penetrate several centimeters below the soil surface. Growth, development and behavior of plant roots are markedly affected by light despite their underground lifestyle. Early studies provided contrasting information on the spatial and temporal distribution of light-sensing cells in the apical region of root apex and discussed the physiological roles of plant hormones in root responses to light. Recent biological and microscopic advances have improved our understanding of the processes involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 111 publications
0
75
0
2
Order By: Relevance
“…Light perceived by photosensory systems in above-ground tissues can affect the roots via long-distance signal transduction pathways [14,15,16,17]. Since sunlight can reach root tissues growing several centimeters underground [18,19,20], Arabidopsis have developed complex photo-sensory systems in the roots to adapt to weak light [21]. Most known plant photoreceptors, including phytochromes, cryptochromes, phototropins, and ultraviolet receptors (UVR), are expressed in the root tissues [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light perceived by photosensory systems in above-ground tissues can affect the roots via long-distance signal transduction pathways [14,15,16,17]. Since sunlight can reach root tissues growing several centimeters underground [18,19,20], Arabidopsis have developed complex photo-sensory systems in the roots to adapt to weak light [21]. Most known plant photoreceptors, including phytochromes, cryptochromes, phototropins, and ultraviolet receptors (UVR), are expressed in the root tissues [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Since sunlight can reach root tissues growing several centimeters underground [18,19,20], Arabidopsis have developed complex photo-sensory systems in the roots to adapt to weak light [21]. Most known plant photoreceptors, including phytochromes, cryptochromes, phototropins, and ultraviolet receptors (UVR), are expressed in the root tissues [21,22]. The light sensory system regulates expression of various related genes under different light intensities and is involved in the development of root structures in response to biotic and abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Three CRYs are encoded in the Arabidopsis (Arabidopsis thaliana) genome: CRY1, CRY2, and CRY3. CRY1 and CRY2 act redundantly in promoting flower induction, sensing blue light as input to circadian clock, and stomatal opening in Arabidopsis (Li and Yang, 2007;Galvão and Fankhauser, 2015;Mo et al, 2015). Both CRY1 and CRY2 regulate primary root elongation, but CRY1 promotes primary root elongation in blue light, whereas CRY2 has the opposite effect (Canamero et al, 2006).…”
Section: Crysmentioning
confidence: 99%
“…1), and CRY1 and CRY2 inhibit root growth via modulation of free auxin levels and polar auxin transport (Mo et al, 2015). The biological function of CRY3 is yet unclear (Song et al, 2006;Klar et al, 2007;Mo et al, 2015). CRYs are nuclear flavoproteins, composed of two domains, an N-terminal photolyase-related region and a C-terminal domain of varying size.…”
Section: Crysmentioning
confidence: 99%
“…In addition to directing root growth towards the gravity vector, sunlight can penetrate the soil up to several millimeters beneath the soil surface, having a direct effect on the growth and development of roots (Woolley and Stoller 1978;Tester and Morris 1987). The red and farred part of the light spectrum can penetrate to greater depths than blue light (Mandoli and Briggs 1984) which has led to plants evolving blue-light receptors located near the upper portion of roots and red-light receptors near the apices due to this pattern of light penetration (Mo et al 2015). In addition, it has been shown that plants utilize blue-light cues to control root architectural features, such as lateral root growth (Moni et al 2015).…”
Section: Introductionmentioning
confidence: 99%